L’anatomie du cheval aux XVIIIe et XIXe siècles : un outil pour mieux représenter le cheval - Christophe Degueurce (In Situ)
The horse’s anatomy in the eighteenth and nineteenth centuries; a tool for representing the horse. The pioneers of the anatomy of the horse were inspired by artistic works such as the horse of the Mattei Villa or the anatomical studies of George Stubbs. Subsequently, scientific knowledge inspired the artists. The approach of Antoine-François Vincent, who was both artist and anatomist, is evidence of the desire to create strong links between the two milieux, driven by the same intentions, namely to produce, breed or represent an animal that was as perfect as possible. The late eighteenth century was a particularly rich period that gave the artists of the nineteenth century the raw materials they would employ in their work.